2001
DOI: 10.1042/cs1010515
|View full text |Cite
|
Sign up to set email alerts
|

Perception of bronchoconstriction in smokers with airflow limitation

Abstract: To our knowledge, no data have been provided as to whether and to what extent dynamic hyperinflation, through its deleterious effect on inspiratory muscle function, affects the perception of dyspnoea during induced bronchoconstriction in patients with chronic airflow obstruction. We hypothesized that dynamic hyperinflation accounts in part for the variability in dyspnoea during acute bronchoconstriction. We therefore studied 39 consecutive clinically stable patients whose pulmonary function data were as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…These findings are consistent with previous studies that have described worse clinical status in subjects with asthma who smoke (8,16,17). Although several studies have reported that smokers with chronic airflow obstruction have fewer symptoms with induced bronchoconstriction than patients with asthma with similar obstruction (49,50), perhaps due to depletion of neurotransmitters from sensory nerves (50), the ability to perceive induced bronchoconstriction could not be predicted by smoking history (49). Taken together, these data demonstrate that laboratory-based testing does not capture the impact of cigarette smoking on disease severity in asthma such as is captured by daily symptom diaries and quality-of-life measures.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are consistent with previous studies that have described worse clinical status in subjects with asthma who smoke (8,16,17). Although several studies have reported that smokers with chronic airflow obstruction have fewer symptoms with induced bronchoconstriction than patients with asthma with similar obstruction (49,50), perhaps due to depletion of neurotransmitters from sensory nerves (50), the ability to perceive induced bronchoconstriction could not be predicted by smoking history (49). Taken together, these data demonstrate that laboratory-based testing does not capture the impact of cigarette smoking on disease severity in asthma such as is captured by daily symptom diaries and quality-of-life measures.…”
Section: Discussionsupporting
confidence: 83%
“…Asthmatic smokers or nonsmokers had variable perception without relationship with bronchial inflammation (114). The data of Ottanelli et al (110) do not seem to show that neutrophils in the sputum have an important independent effect on the perception of bronchoconstriction by patients with permanent bronchial obstruction.…”
Section: Clinical Correlatesmentioning
confidence: 68%
“…The perception of dyspnoea is abnormal in COPD, but the situation seems to be different from that observed in asthma (108,109). Ottanelli et al (110) suggested that tobacco has an effect on abnormal perception associated with the sputum neutrophilia, which is often observed during persistent obstruction in severe asthma and smoker COPD (111)(112)(113). Asthmatic smokers or nonsmokers had variable perception without relationship with bronchial inflammation (114).…”
Section: Clinical Correlatesmentioning
confidence: 99%
“…The diagnosis of COPD is based upon data from medical history, physical examination, and results from pulmonary function testing (Kumar & Gross, 2002). One barrier to accurate diagnosis in older patients is that age seems to reduce the perception of bronchoconstriction leading to less reporting of milder symptoms and thus underdiagnosis (Ottanelli et al, 2001).…”
Section: Pathophysiology Of Copdmentioning
confidence: 99%